(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this article will talk about the practical importance, aspects, and experience of the digital economy. In the context of today’s rapidly developing global economy, the digital economy is at the beginning of its development, first of all it is illuminated that it is able to significantly increase the standard of living of people, and this is its main benefit. Also in the article are mainly the further development of the digital economy and the elimination of moammos in it, the impact of the growth of the digital economy on global economic growth, the role of the digital economy in the world market. it has also been highlighted that it is able to significantly change the way people live and that this is its main benefit.